Applicability of auriculotherapy in cancer patients: an integrative literature review - Contim, Carolina Lélis Venâncio; Espírito Santo, Fátima Helena do; Moretto, Isadora Górski (Revista da Escola de Enfermagem da USP, 2020)
Objective To analyze scientific evidence in the literature on the use of auriculotherapy to relieve symptoms related to cancer and/or its treatment. Method An integrative literature review based on: MEDLINE, CINAHL, LILACS, SCOPUS and COCHRANE in the last five years in English, Portuguese and Spanish. Inclusion criteria primary studies with the central theme. Exclusion criteria opinion articles, reviews and experience reports. Results The search resulted in 435 publications, but only 11 remained after applying four selection stages. An analysis of the study designs showed that three of them (27.5%) had a high level of evidence, three (27.5%) had moderate, four (36%) had low and one (9%) had a very low level. The evaluated outcomes were related to the following symptoms: pain, constipation, nausea and vomiting, hot flashes, dyspnea, fatigue and insomnia. Moreover, 100% of the publications exposed positive effects of auriculotherapy in oncology. Conclusion Auriculotherapy in cancer patients improves symptoms, and this practice was considered a safe and acceptable intervention. However, it is necessary to expand studies to obtain more favorable evidence since only 3 studies presented a high level of evidence.